2022
DOI: 10.1177/02683555221114542
|View full text |Cite
|
Sign up to set email alerts
|

Conservative therapy significantly reduces patients’ chronic venous disease symptoms: A Caribbean insight into the VEIN Act Program

Abstract: Objectives We sought to determine the baseline demographic and clinical characteristics of patients with Chronic Venous Disease (CVD) across the Caribbean, and to evaluate patients’ compliance to conservative therapy and the effectiveness of such therapy in reducing patients’ CVD symptoms. Method Patients were enrolled into the VEIN Act Program, and their demographic data, CVD symptoms (and their intensity) and CEAP C-classification was recorded at the first visit. Patients were prescribed conservative therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Despite the worsening of symptoms of CVI during hotter weather, there was no association found between climate and discomfort due to heat as a reason for non‐compliance. For example, a Caribbean study found that sweating was only a minor reason (9.1%) for non‐compliance 31 . In the same instance in a Abidjan (West Africa) study heat was not a reason, however, the work environment was selected by 8.7% of participants and it was found that the participants who were less compliant due to work environment were working at multiple sites 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the worsening of symptoms of CVI during hotter weather, there was no association found between climate and discomfort due to heat as a reason for non‐compliance. For example, a Caribbean study found that sweating was only a minor reason (9.1%) for non‐compliance 31 . In the same instance in a Abidjan (West Africa) study heat was not a reason, however, the work environment was selected by 8.7% of participants and it was found that the participants who were less compliant due to work environment were working at multiple sites 33 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Compliance rates were generally highest in the studies where participants were prescribed GCT and were reviewed at a follow-up appointment between one week and three months after prescription. [29][30][31]39 There was a correlation found between disease severity and likelihood of compliancy, where with VLUs participants were more compliant than participants with earlier stages of CVI. [35][36][37][38][39]43 Another study that only interviewed participants who were always noncompliant found that many participants did not know VVs were a condition with serious complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological treatment with venoactive drugs (VADs) can improve venous tone and contractility, reduce edema and inflammation, and improve microcirculation [ 2 ]. The main modes of action of VADs are decreasing capillary permeability and reducing release of inflammatory mediators [ 1 ].…”
Section: Introductionmentioning
confidence: 99%